2019
DOI: 10.1177/0003702819837297
|View full text |Cite
|
Sign up to set email alerts
|

Lighting the Ivory Track: Are Near-Infrared and Chemometrics Up to the Job? A Proof of Concept

Abstract: A rapid tool to discriminate rhino horn and ivory samples from different mammalian species based on the combination of near-infrared reflection (NIR) spectroscopy and chemometrics was evaluated. In this study, samples from the Australian Museum mammalogy collection were scanned between 950 nm and 1650 nm using a handheld spectrophotometer and analyzed using principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). An overall correct classification rate of 73.5% was obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…We found that the PCA loadings associated with the first PC were observed around 1075 nm, 1200 nm and 1400 nm corresponding with N–H and O–H overtones were the most important. 2 The PLS-DA model developed correctly classified more than 74% of the samples in the entire data set. While Rhino samples were classified correctly (95%) elephant, walrus and hippo samples yield low to intermediate classification rates (between 60 and 75%).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…We found that the PCA loadings associated with the first PC were observed around 1075 nm, 1200 nm and 1400 nm corresponding with N–H and O–H overtones were the most important. 2 The PLS-DA model developed correctly classified more than 74% of the samples in the entire data set. While Rhino samples were classified correctly (95%) elephant, walrus and hippo samples yield low to intermediate classification rates (between 60 and 75%).…”
Section: Resultsmentioning
confidence: 97%
“…Similar results were reported by other authors where ivory samples were analysed using short wavelengths in the NIR region. 2,1315…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations